Endodontic management of bilateral mandibular canines with an unusual root canal anatomy - Sujan Rijal; Amit Yadav; Karthik Shetty (Wolters Kluwer Medknow Publications, 2015)
This case report describes the endodontic management of bilateral mandibular canines with unusual root canal anatomy in a patient. The right mandibular canine had two separate roots (buccal and lingual), each root having a single canal. The left mandibular molar had two separate canals coronally joining into a single canal in the apical 3 rd (Vertucci Type II). While the presence of two roots and two canals in one root is not uncommon, finding a combination of these morphological variations in the same patient has not been reported previously. This emphasizes the perception of the clinician that a given tooth will contain a specific number of roots and/or root canals canal should be changed, and such variations should be kept in mind during the endodontic treatment of permanent mandibular canines.